Tertiary Pharmaceutical Care Services: Facts and Realities - Briano, Ogbonna (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
Pharmacy practice is dynamic, evolving and requires high level of drug knowledge in clinicaljudgment, decision making and advanced skills in actively and systematically identifying andresolving patients pharmacotherapy problems for desired outcomes to be achieved in patientcare. This study organized literatures and identified the evidence based and ever increasing rolesof pharmacists in tertiary pharmaceutical care. Literature search was conducted in Embase, Medline and Cochrane for evidence based studies describing pharmacist’s tertiarypharmaceutical care. Studies were selected based on their relivance to the subject, existingtheories and models, and were summarized based on qualitative level. Results indicated thatclinical pharmacist led pharmaceutical care improved clinical, economic, and humanisticoutcomes in tertiary care settings. Pharmacists’ roles have evolved from a product to costeffective patient oriented services.